Airglow imaging observations of some evolutionary aspects of equatorial plasma bubbles from Indian sector. Issue 2 (15th July 2019) - Gurav, O.B.; Narayanan, V.L.; Sharma, A.K.; Ghodpage, R.N.; Gaikwad, H.P.; Patil, P.T.
Abstract: The ground-based all sky imager (ASI) is an advanced optical technique, capable of measuring the strong F-region nightglow in OI 630.0 nm emission from atomic oxygen. This emission is used to study the large-scale F-region plasma irregularities; called as Equatorial Plasma Bubbles (EPBs) which often disturbs the communication and navigation systems over low latitudes. The observations of OI 630.0 nm nightglow emission have been carried out from low latitude station Kolhapur (16.8°N, 74.2°E, 10.6° dip. lat.) using ASI during moonless nights for the period of 2011 to 2015. We have analyzed images recorded by ASI during this period and found some interesting features of EPBs on few nights (08 cases). This paper reports the analysis and the dynamics of EPBs features such as bifurcation, merging and detachment. The bifurcation in EPBs occurs before mid-night and extends to couple of hours towards dawn. Also, the secondary structures are seen as evolving features on the eastern wall of EPBs. In one of the case, the EPBs are seen to merge with each other due to their opposite tilts. Also, some EPBs detach due to unequal drifts along the meridian indicating the presence of strong latitudinal gradient in zonal neutral winds or altitudinal shear in zonal plasma drift which might be responsible for this detachment. In some cases we note that the EPBs shrink. Some of these features support the previous findings and some are new which needs further detailed investigation.